HUBUNGAN DUKUNGAN SOSIAL SUAMI DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI DESA MADUREJO PRAMBANAN - Siti Alifah Yuliana; Yuli Ernawati; Heni Febriani (STIKES Wira Husada Yogyakarta, 2019)
the forerunner of healthy succession from an early age. Infants who are not given exclusive breastfeeding will increase the risk of various dideases such as diarrhea an pneumonia. With exclusive breast milk, 55% of infant deaths from diarrhea and Upper Respirstory Tract Infection can be prevented in infants aged 0-3 months and 66% in infants aged 4-11 months.1 Exclusive breastfeeding practices are influenced by many factors, one of which is husband’s support.Objective: To find out the relation between husband’s social support and the success of exclusive breastfeeding in Madurejo Prambanan Village. Methods: The type of research is an analytic survey with the sample of 64 respondents, this study used a cross sectional approach. The subjects were nursing mothers who had children aged 7-12 months. The research tool used in the research is questionnaire and data analysis used Chi Square test.Result: Husband’s support level in exclusive breastfeeding in Madurejo Prambanan Village was good for as many as 61 people (95,3%). Respondents who did not succed in giving exclusive breastfeeding were as many as 31 people (48,4%). Meanwhile, the relation between the two variables is there is no relation between husband’s social support with the success of exclusive breastfeeding in Madurejo Prambanan Village with p-value > (0,05) yaitu 0,592.Conclusion: There is no relation between husband’s social support and the success of exclusive breastfeeding in Madurejo Prambanan Village.